PENINGKATAN PEMAHAMAN DAN KEMAMPUAN SISWA SMP NEGERI 2 SINGARAJA DALAM MENGGUNAKAN MEDIA SOSIAL SECARA BIJAK BERDASARKAN UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Dewa Gede Sudika Mangku; Ni Putu Rai Yuliartini (Jurnal Pengabdian Kepada Masyarakat Media Ganesha, 2020)
The development of increasingly widespread pornography cannot be separated from the development of today's communication technology. Pornographic content that was originally distributed via Digita Versatile Disk (DVD) or Versatile Compact Disk (VCD), can now be accessed easily via laptops, tablets, smartphones, and other digital devices supported by an internet connection. This program is a terminal program in order to increase the Understanding and Ability of SMP Negeri 2 Singaraja Students in Using Social Media Wisely Based on the Information and Electronic Transactions Law, carried out with a ball pick-up system. In its implementation, this program will refer to a synergistic pattern between experts and practitioners from the Ganesha University of Education and related agencies, namely the Office of Education. On the other hand, this program is also directed at creating a collaborative and democratic climate of cooperation between the world of higher education and society at large under the coordination of related agencies. Based on the above, this program is closely related to the Tri Dharma of Higher Education, namely the third dharma concerning community service. The rapid development of internet technology has made it possible for computers to load and display various forms of media on it. The use of the internet and social networking web can not only make a positive contribution to students' academic activities but also to teachers. The internet and social networking web can provide the possibility for teachers to explore and exchange information and knowledge in the subjects they cover. Through the use of the internet and social networking websites, teachers will always be ready to teach up- to-date knowledge to students. This of course requires the ability of the teacher himself to actively access the website in the field that is his expertise. This is in line with the definition or meaning of media devices and learning technology in schools in a broad sense, which includes hardware, software, and human resources that can be used to enrich students' learning experiences. With the cooperation of a good service team and the active participation of resource persons in this activity, everything can go as expected. So that later the implementation of this program will continue, namely an evaluation of the implementation of the program can be carried out immediately, and it is hoped that later it will be able to produce outcomes that are in line with the expectations of the implementing team for this community service program.